Iceland : Selected Issues. - International Monetary Fund. European Dept. (Washington, D.C. : International Monetary Fund, 2019)
This Selected Issues paper examines scope for improving Iceland's fiscal framework. Iceland's fiscal framework provides for a forward-looking exercise in consolidated fiscal planning. The Icelandic fiscal framework shares most elements of successful fiscal frameworks but would benefit from more structured guidance in dealing with cyclical fluctuations. It is backed by a firm legal basis that reflects political support for the fiscal policy objectives, covers the consolidated general government, and is based on sound accounting practices and budget management arrangements. The current parameters of the policy rules have a bias to reduce net public debt and gradually build fiscal space to deal with adverse shocks to economic activity. Adding a primary structural balance rule to the framework would ensure a countercyclical fiscal policy but would add significant complexity. Once the net public debt reaches a socially desirable level, the fiscal rule parameters may be modified to keep net public debt fluctuating around that level.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet